2023
DOI: 10.1055/a-2019-5131
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Surgical Pathway in Permanent Facial Filler Removal

Abstract: Although permanent fillers have been introduced in order to get long lasting results, many studies have shown numerous severe and disfiguring complications. Non-surgical procedures may mitigate those adverse events but the only way to remove the filler previously injected is represented by surgical excision. We present a pathway of facial surgical accesses to be performed achieving two goals: permanent filler removal and restore facial aesthetic balance. The proposed surgical accesses are already standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…In our study, we performed a different surgical approach, with a chalazion clamp and diode laser for hemorrhagic control and then a simple suture. Pascali et al [50] declared that nonsurgical procedures might not be enough to treat problems as our case reported, and they confirmed that the only way to remove the filler previously injected was represented by surgical excision. The authors presented a pathway of facial surgical accesses to treat 231 patients, achieving permanent filler removal and restoring facial esthetic balance.…”
Section: Discussionsupporting
confidence: 75%
“…In our study, we performed a different surgical approach, with a chalazion clamp and diode laser for hemorrhagic control and then a simple suture. Pascali et al [50] declared that nonsurgical procedures might not be enough to treat problems as our case reported, and they confirmed that the only way to remove the filler previously injected was represented by surgical excision. The authors presented a pathway of facial surgical accesses to treat 231 patients, achieving permanent filler removal and restoring facial esthetic balance.…”
Section: Discussionsupporting
confidence: 75%